Motivasi Belajar Siswa dengan Media Boneka Tangan pada Pembelajaran Tema 4 Kelas II di Masa Pandemi: Naratif Inkuiri - Salim, Nurazizah; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Learning is a complex process that occurs in everyone throughout their life. The learning process occurs because of the interaction between a person and their environment. Therefore, learning can happen anytime and anywhere. One sign that someone has learned is a change in behaviour in the children. This research was conducted to increase students' learning motivation through hand puppet media in learning theme 4 about clean and healthy living for second-grade students during the pandemic. This study used a qualitative approach with the narrative inquiry method. The subjects of this research are teachers and students. Through research instruments in the form of field notes, storytelling, and documentation, the researcher conducted research in class II with 10 students. The results showed that increasing students' learning motivation through hand puppet media in learning theme 4 about clean and healthy living with a high level of curiosity, doing assignments, and collecting assignments in the learning carried out in class II at the State Elementary School of Gunung Datar was quite good. Because every student is always enthusiastic every day, seeing the changes that are considered quite good are carried out according to their abilities with the help of the teachers and also the parents in increasing learning motivation in class II at the State Elementary School of Gunung Datar, even though it is not optimal or not perfect.